Prospects, challenges and institutional linkages of vegetable value chain in Ibadan city of Nigeria - Olajide-Taiwo, L. O.; Bamimore, K.; Olajide-Taiwo, F. B.; Cofie, Olufunke O.; Babajide, K. S. (2014)
The entire population of over 2.5 million people living in Ibadan city of Nigeria depends on farmers within and around the city to supply up to 80% of their vegetables, estimated at about 900 tonnes per day. This study was carried out to establish the presence, types, systems and institutional linkages influencing the urban and peri-urban vegetable-value chain in the city. Three local government areas (LGAs), comprising two urban and one peri-urban LGA were chosen among the 11 which make up the metropolitan city for the study. They were selected because of their high number of agricultural activities. From the estimated list of 5,082 farmers in the selected LGAs, 210 respondents were randomly selected. Data were collected from the farmers using a schedule of structured interviews. Marketers, processors and supplies dealers were also interviewed using focal group discussions of between 8 and 10 interviewees per session to generate qualitative data about their involvement in the vegetable-value chain in the city. Other stakeholders, in particular key informants from institutions (academic and research institutions, and extension, health, land and finance services) were interviewed. Because of the exploratory nature of the study, data were analyzed with descriptive (frequency counts, percentages, measures of central tendencies) statistics and rankings. An informal network of producers-marketers-consumers exists for the vegetable value chain in the city. The network provides income ranging from N 50,000.00-500,000.00 (N 150 = $ 1.00) per annum for participants based on activities within the chain. Vegetables (Amaranthus, Corchorus, Celosia, okra and pepper) production accounts for 42% of the crop production enterprise. The crops are planted on roadsides (23%), in backyards (22%), and near streams (14%), among other locations. Inadequate finance ranked highest among the listed constraints, and institutional linkages are weak. Concerted and conscious efforts with enabling policies should be instituted to attain the full potential of the vegetable-value chain in the city of Ibadan.